Outcome Between Intralesional Injection of Triamcinolone following Optical Internal Urethrotomy (OIU) and OIU Alone for the Management of Short Segment Stricture of male Urethra (Journal of Dhaka Medical College, 2021)
Objective: To compare the outcome of optical internal urethrotomy (OIU) with or without intralesional triamcinolone acetonide injection for the treatment of short segment anterior urethral stricture.Methods: This prospective quasi experimental study was carried out in the department of Urology, DMCH, Dhaka from November 2015 to April 2017 on 50 patients with short segment of anterior urethral stricture. Cases were randomly allocated to group A (OIU without Triamcinolone) and group B (OIU with Triamcinolone). Each group consisted of 25 patients. Data were analyzed and compared by statistical tests.Results: There were no significant differences in the baseline characteristics of the patients. Recurrences of stricture urethra were higher among those without Triamcinolone than cases with Triamcinolone which was statistically significant (p=0.033) at 6 month and (p=0.016) at 9 months. Regarding mean time interval in month of development of recurrence of stricture was 6.1±1.66 months in Group A and 7.66±1.52 months in Group B which was statistically significant (p=0.001)Conclusion: OIU with intralesional triamcinolone is better than OIU alone. It significantly reduced and delayed the recurrence of anterior urethral stricture.J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 126-130